SISTEM KOMUNIKASI METEOR BURST UNTUK KOMUNIKASI BERGERAK - Bazergan, Abdullah
This thesis is concerned with data transmission through mobile meteor burst communication system. Mobile communication which is used meteor burst represents mobile communication system that is recently developed ( around 80's decade). Meteor burst communication system has character of Space Division Multiple Access (SDMA) inherently. In fixed MBC, the Space Division Multiple Access (SDMA) is the commonly used method for data transmission in which the meteor covers only one user, in another words, only one user can respond at a certain time. A problem will appear when one meteor covers more than one user according to a certain conditions which make the area of the meteor trail becomes larger. This will cause collision among the users which are closed to each other during the response. Here spread spectrum technique is used to avoid collision caused either by large network or when remote station nodes are closely spaced Also, coding technique Bose-Chauduri-Hocquengham (BCH) is used here in order to improve the performance of the system. As one of these techniques, code division multiple access (CDMA) has been chosen as a solution to this problem. The performance of the system is measured by cakulating the waiting time and the throughput of the CDMA for different number of simultaneous users. The result of simulation show that, for a certain number of channel, the increasing number of user will decrease the performance of the system. The performance will be improved by increasing the number of the channel and using coding technique with error correction.